The first X-ray spectrum of the high-mass X-ray binary XTE J1855−026 during the compact object eclipse. Issue 1 (10th February 2022) - Sanjurjo-Ferrín, G; Torrejón, J M; Rodes-Roca, J J
ABSTRACT: We present the first XMM–Newton observation of the classical supergiant high-mass X-ray binary XTE J1855−026 taken entirely during the eclipse of the neutron star (NS), covering the orbital phases ϕ = 0.00–0.11. The analysis of the data allows us to (a) compare with the parameters obtained during the existing pre-eclipse observation and (b) explore the back-illuminated stellar wind of the B0I-type donor. The blackbody component, used to describe the soft excess during pre-eclipse, is not observed during eclipse. It must be then produced near the NS or along the donor–NS line. The 0.3–10 keV luminosity during eclipse (∼10 34 erg s −1 ) is 70 times lower than pre-eclipse. The intensity of the Fe Kα line, in the average eclipse spectrum, is ∼7.4 times lower than the one measured during pre-eclipse. Since Kα photons cannot be resonantly scattered in the wind, the vast majority of Fe Kα emission must come from distances within 1 R * from the NS. The eclipse spectrum is successfully modelled through the addition of two photoionized plasmas, one with low ionization (log ξ1, cold  = 0.36) and high emission measure (EM1, cold ≈ 3 × 10 59 cm −3 ) and another with high ionization (log ξ2, hot  = 3.7) and low emission measure (EM2, hot ≈ 2 × 10 56 cm −3 ). Assuming that the cold and hot gas phases are the clumps and the interclump medium of the stellar wind, respectively, and a clump volume filling factor of ≈0.04–0.05, typical for massive stars, a density contrast between clumps and the interclump medium of n c / n i ≈ 180 is deduced, in agreement with theoretical expectations and optical–ultraviolet observations of massive star winds.